Latinoamérica ante la guerra contra Gaza - Tawil Kuri, Marta (El Colegio de México A.C., 2024)
The texts in this Special Section, resulting from the forum “Latin America and the war against Gaza: A preliminary assessment”, gather the analyses that various specialists in Mexico and Latin America prepared on the reactions of different Latin American governments to what took place in Israel on October 7, 2023 and in the Gaza Strip since then. I am grateful for the commitment of the colleagues who agreed to participate in this initial dialogue on a crucial issue of the human and international security agenda.